THE IMPACT OF DISEASE AND HARVESTING ON THE DYNAMICAL BEHAVIOR OF PREY PREDATOR MODEL - Naji, Riad; Ibrahim, Hiba (Iraqi Journal of Science, 2024)
In this paper, a harvested prey-predator model involving infectious disease in prey isconsidered. The existence, uniqueness and boundedness of the solution arediscussed. The stability analysis of all possible equilibrium points are carried out.The persistence conditions of the system are established. The behavior of the systemis simulated and bifurcation diagrams are obtained for different parameters. Theresults show that the existence of disease and harvesting can give rise to multipleattractors, including chaos, with variations in critical parameters.